Investigating The Performance Of Local And Indigenous Businesses In Times Of Economic Recession With Emphasis On Developing The Capabilities Of Cooperatives In Sistan And Baluchestan Province - Ali Asghar Tabavar; Abdoulnaser Derakhshan; Sahar Arefi (پژوهش‌های مدیریت عمومی)
AbstractToday, economic stagnation, job creation, and environmental issues are of concern to different countries of the world, including Iran. In this regard, a cooperative in the country can be a solution to overcome the existing unfavorable economic and social conditions, including the weakness in creating employment for young people and social capital, economic stagnation, and environmental problems in the country. The purpose of the current research is to investigate the performance of local and local businesses in the economic recession with an emphasis on the development of the capabilities of cooperatives. Vector error correction models are used to test the research hypothesis. This test evaluated the effects of the variables in the long term and also examined the reaction of the variables to the shock of the periods of economic recession. Data analysis was done using EViews software.Based on statistical findings, it can be claimed that cooperatives can improve business performance in the long term by creating and collecting capital. At the confidence level of 0.95, the value of the t-statistic was estimated at 9.683, and it is significant. Also, the cooperatives of Sistan and Baluchistan province can improve the performance of local businesses in the long run by increasing the number of working people.IntroductionThe term "cooperation" generally refers to assistance, helping, observing collective interests, and arresting others, which simply means "cooperation". In contrast to its specific meaning, cooperation implies a specific type of working with each other that enables access to common goals through the formation of a formal organization and the use of specific management methods. When a person cannot work alone, it is better to get help from others to do the work collectively and with each other's cooperation. This way of doing work is called "cooperative" and its organized form is called cooperative. Today, economic recession, job creation, and environmental issues are of great concern to countries, including our country. In this regard, the model of cooperative companies can be a way to overcome problems and crises, and it can also be a solution to overcome the existing unfavorable economic and social conditions, including the weakness in creating employment for young people and social capital, economic stagnation and environmental problems in the country.Because of the lack of success of cooperatives in the country, the country's economic challenges and problems intensified, on the other hand, the cooperative movement itself can be a factor for increasing solidarity among people with experience of successful collective work based on trust, which also leads to economic prosperity. Also, with the lack of success of this movement, the social and economic structural problems of the country will intensify. In general, it can be said that cooperatives, as economic and social organizations, have the necessary power and capacity to organize different classes and groups of people to create sustainable human development, and during the economic recession, they play an effective role in creating stable employment and income generation (Shadmehri, Ahmad 2005).Case studyThe statistical population of the research included the collection of managers, supervisors, and employees of cooperatives located in Sistan and Baluchistan province in the number of 345 people, out of which 182 people were randomly selected as the sample group.Materials and methodsThe current research is of an applied type, Also, this research is one of the empirical research in the field of management. The statistical population of the research includes local businesses and cooperative companies of Sistan and Baluchistan province, which have been investigated over a 20-year period.The model and measurement indicators are as follows: The performance of indigenous and local businesses: this variable is measured through the added value created by indigenous businesses in Sistan and Baluchistan province. In order to measure this variable, the amount of changes in the added value created as a percentage of changes in the profit of these companies is considered.Economic recession: In the context of the economic cycle, an economic recession is a period when the economy takes on a state of contraction and shrinks. In other words, economic growth in this period is negative. This period is usually defined as two consecutive 3-month periods. A more general definition of economic recession is a significant decrease in activity in the entire economy that lasts at least a few months. Development of the capabilities of cooperatives: this variable is measured through the number of people employed in active cooperatives and the amount of capital changes of members.Discussion and Results Vector error correction models are used to test the hypothesis of the research. This test evaluates the effects of variables in the long term and also examines the reaction of variables to the shock of periods of economic recession. The first step in carrying out the estimation approach of vector error correction models is to check the meanness of the data. Therefore, the significance of all variables is checked and if some of them are insignificant, the significance variables are formed using measurement methods. Then, by examining co-accumulation, the existence of a long-term relationship between the variables is tested, and by confirming the assumption of the existence of a long-term relationship between the variables, certain scientific results are extracted using the VECM model. Data analysis was done using EViews software. According to the findings of the vector error correction model (VECM), the Bland mat equation can be reported as follows.PERF = 10.11+0.047 CAP +0.516 INFL -1.237 DUMMYIn the long term, cooperatives can improve business performance by creating and collecting capital. At the confidence level of 0.95, the value of the t-statistic was estimated at 9.683 and it is significant. Also, the cooperatives of Sistan and Baluchistan province can improve the performance of local businesses in the long run by increasing the number of working people.ConclusionToday, attention to employment and environmental issues has been given much attention by organizations and people. Environmental, organizational, and extra-organizational factors are the reasons that create conditions that lead organizations and individuals in this direction. For a deep understanding of the concepts of cooperatives and indigenous and local businesses and economic stagnation, a clear definition of them is vitally important because the definition means the implementation of the desired model.Usually, after the formation of the cooperatives, to empower and create skills in the present people, they plan programs related to the purpose of forming the cooperative. Empowerment of local people and presence in domestic and local businesses leads to the growth of these businesses and increases self-confidence in creating a local business for local people. The ability of people in the field of ecotourism can be among the newest businesses at the native and local levels. On the other hand, the beneficiaries present in the cooperatives can also benefit from the financial support of the cooperative and boost their business. According to the existing capacities and potentials in Iran, the field of ecology or ecotourism can lead to great growth and the impact that local businesses in the field of ecology through cooperatives can have on economic growth and national development. It is undeniable. Preservation of the environment and responsibility towards society are among the important fields in the sustainability of today's businesses. Therefore, it can be said that green entrepreneurship, which is a new topic in the science of entrepreneurship, can have a significant impact on the sustainability of business and its development. On the other hand, in the area of ​​businesses related to the environment, there are also opportunities to create businesses that can develop native and local businesses by interacting with the environment and paying attention to it. The primary goal of creating cooperatives is to help increase employment. The most important contribution that cooperatives can make to the local business sector of any country is the growth of the employment sector of rural communities. He considered this important through the attention of cooperatives to entrepreneurship and also entrepreneurship in the ecotourism industry, innovation in green businesses. According to the obtained results, the development of the capabilities of cooperatives in economic recession conditions, employment creation of cooperatives, empowerment, and green entrepreneurship affects the performance of native and local businesses. Also, the development of cooperatives affects the performance of ecotourism.